Where does liver fat go? A possible molecular link between fatty liver and diabetes. Issue 2 (5th October 2016) - Kikuchi, Akihiro; Takamura, Toshinari
Abstract : An elevation of fatty acid delivery amplifies the TCA cycle flux with a rise in anaplerosis/cataplerosis, leading to a proportional rise in oxidative stress and inflammation in liver.